Primary biliary cholangitis. Treatment options in 2025. A narrative review - Angelara, Maria; Papachristou, Klairi; Papatheodoridi, Margarita; Nasiri-Ansari, Narjes; Karagiannakis, Dimitrios S.; Androutsakos, Theodoros (Frontiers in Immunology, 2025)
Primary biliary cholangitis (PBC) is a chronic, cholestatic disease with a female predominance and a long disease duration. The pathogenesis of PBC is still unclear; however, genetic, epigenetic, and environmental factors, alongside immune dysregulation, seem to lead to a dysfunction of the biliary ‘bicarbonate umbrella’ and increased biliary epithelial cells apoptosis. Ursodeoxycholic acid (UDCA) has been the treatment of choice for PBC since its approval back in 1994; however, a percentage varying from 15-40% of all patients fail to achieve biochemical response or alkaline phosphatase normalization. Obeticholic acid, though promising at first, failed to show benefit after long-term use and was retracted from the market. Two peroxisome proliferator–activated receptor agonists (PPARs) have recently been approved for use in patients with PBC, showing biochemical response in non-responders and improvement of pruritus. However, a substantial percentage of patients fail to achieve serum alkaline phosphatase and bilirubin normalization; as a result, many drugs with different mechanisms of action are in phase 2 or 3 trials. The aim of this review is to present available data regarding PBC treatment and explain the pathogenetic pathway each one targets.